2017
DOI: 10.1111/flan.12306
|View full text |Cite|
|
Sign up to set email alerts
|

The Effectiveness of Video‐Based Shadowing and Tracking Pronunciation Exercises for Foreign Language Learners

Abstract: This exploratory classroom study investigated the effects of two video‐assisted pronunciation interventions on the French pronunciation of 12 males and 7 females (n = 19) enrolled in a fourth‐year high school French class. Interventions occurred three times per week over a semester and required participants to repeat what they heard while watching subtitled, cultural videos in French—both during class and in self‐directed computer‐lab exercises. Researchers assessed the improvement in pronunciation performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
(58 reference statements)
2
19
0
Order By: Relevance
“…This was indicated by comparing mean scores of the experimental group students in the pre-post administration of the reading attitude survey. Results of the present study is consistent with results of previous studies that showed the effectiveness of using shadowing technique on developing some EFL learners' skills (Babapour et.al, 2018 ;Commandor & Guerrero , 2013 ;Foote & McDonough , 2017 ;Hamzar , 2014;Hamadr , 2016;Januarty & Asib & Suparno , 2018 ;Martinsen et al ,2017 ;Mitterer &Ernestus , 2008 ;Sadeghi et. al., 2016;Teeter , 2017 ;Zuhriyah , 2016).Moreover , the correlation between oral reading fluency and comprehension was found ( r=0.873) , which is consistent with findings of other studies (Price et al, 2016 ;Howland & Scott , 2016).…”
Section: Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This was indicated by comparing mean scores of the experimental group students in the pre-post administration of the reading attitude survey. Results of the present study is consistent with results of previous studies that showed the effectiveness of using shadowing technique on developing some EFL learners' skills (Babapour et.al, 2018 ;Commandor & Guerrero , 2013 ;Foote & McDonough , 2017 ;Hamzar , 2014;Hamadr , 2016;Januarty & Asib & Suparno , 2018 ;Martinsen et al ,2017 ;Mitterer &Ernestus , 2008 ;Sadeghi et. al., 2016;Teeter , 2017 ;Zuhriyah , 2016).Moreover , the correlation between oral reading fluency and comprehension was found ( r=0.873) , which is consistent with findings of other studies (Price et al, 2016 ;Howland & Scott , 2016).…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…Recently, there has been an increasing amount of literature on investigating the impact of shadowing technique with different aspects of EFL learning process, such as , comprehension (Babapour et al, 2018, Sadeghi et al, 2016, speaking skills (Hamzar, 2014;Januarty, Asib & Suparno, 2018), intonation (Hsieh, ISSN 1110-2721 Dong & Wang, 2013), pronunciation (Martinsen et al, 2017;Foote & McDonough, 2017), listening skills (Zuhriyah, 2015, Hamadr, 2016, speech perception (Mitterer & Ernestus, 2008) and motivation (Teeter, 2017).…”
Section: Issn 1110-2721mentioning
confidence: 99%
“…First, global proficiency was operationalized as listeners’ intuitive judgments of comprehensibility, perceived fluency, and accentedness (e.g., Levis, Sonsaat, Link, & Barriuso, ). Under this, intelligibility was analyzed not only through listener transcription (e.g., Derwing et al., ) but also through their judgments (e.g., Martinsen, Montgomery, & Willardson, ). Second, experts’ subjective ratings of specific aspects of pronunciation proficiency were operationalized as experts’ ratings of segmental (e.g., Lee & Lyster, ), prosodic (e.g., Hardison, ), and temporal (e.g., Gorsuch, ) qualities.…”
Section: Research Synthesis and Meta‐analysismentioning
confidence: 99%
“…Globally considered, there has recently been a revival of interest in pronunciation teaching to make L2 learners more efficient users of the target language (Luchini, 2005), and this interest has been more apparent as a number studies have been published in leading journals in ELT (e.g., Ali, 2016;Engwall, 2012;Golonka, Bowles, Frank, Richardson, & Freynik, 2014;Hsu, 2016;Lee & Lyster, 2016;Liakin, Cardoso, & Liakina, 2017;Luo, 2016;Martinsen, Montgomery, & Willardson, 2017;Mbah, Mbah, Iloene, & Iloene, 2014;Meng, Wang, Li, Meng, & Chen, 2012;Mompean & FouzGonzález, 2016;Olson, 2014;Ouni, 2014;Sun et al, 2017;Thomson, 2011Thomson, , 2012Thomson & Derwing, 2015;van Doremalen, Boves, Colpaert, Cucchiarini, & Strik, 2016). The EIL and LFC perspective has had a great impact on this.…”
Section: )mentioning
confidence: 99%
“…In line with such studies, some researchers with the same line of thought claimed that improvement in pronunciation is beyond the control of teachers because motivation and L1 are the most prominent predictors of success in pronunciation. On the other hand, others provided evidence that formal training could contribute to attainment (e.g., Bongaerts, 1999;Couper 2003;Derwing, Munro & Wiebe 1998;Kissling, 2014;Martinsen, Montgomery & Willardson, 2017;Rezaei, Gowhary & Azizifar, 2015). Such mixed results were probably due in part to various objectives of instruction, diverse groups of students and methodologies involved as well diverse testing procedures (Thomson & Derwing, 2015).…”
Section: Introductionmentioning
confidence: 99%